Staff perceptions of the covid-19 contact tracing system in the Ekurhuleni Health District, 2020 - Muropa, Mazvita Naome Mberi nee (My University, 2022)
Background: COVID-19 Contact tracing has been shown to avert outbreak propagation by preventing secondary infections from COVID-19 cases. There is a paucity of information on implementing functional, effective contact tracing. Objectives: The aim of our study was to study contact tracing implementation and the barriers and facilitators of contact tracing implementation in the Ekurhuleni Health District (EHD). Methodology: A total of 118 Contact tracers (CTs) completed self-administered questionnaires, and 22 managers were interviewed. Results: Equipment availability (54/118, 45.8%), accurate client information (85/118,72.0%), client cooperation (47/118, 39.8 %) and willingness to engage with health services (40/118, 33.9%), effective planning and communication (33/118, 28,.0%) were important facilitators to finding and following up contacts and managing symptomatic contacts. Conclusions: Data quality and resource availability were key barriers or facilitators to contact tracing implementation for both managers and tracers. The use of telephonic contact tracing methods was perceived to improve tracing efficiency, while physical contact tracing was perceived to improve tracing effectiveness. Recommendations: Early, effective community engagement, staff support, and the availability acceptable, effective information management systems and guidelines will facilitate better contact tracing implementation in the future.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Medicine in Community Health to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, 2022